SPORT AS AN ELEMENT OF CLUSTER TECHNOLOGY FOR A HEALTHY LIFESTYLE - Umaraliyeva Dilfuzi Umarali kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article highlights the topic of the methodology of developing exercises and the development of ailments. In the final part, recommendations are given on the use of innovative technologies in teaching students general developmental gymnastic exercises.